Evaluation of the resilience of a full-scale down-flow hanging sponge reactor to long-term outages at a sewage treatment plant in India. (1st October 2016) - Onodera, Takashi; Takayama, Daisuke; Ohashi, Akiyoshi; Yamaguchi, Takashi; Uemura, Shigeki; Harada, Hideki
Abstract: Resilience to process outages is an essential requirement for sustainable wastewater treatment systems in developing countries. In this study, we evaluated the ability of a full-scale down-flow hanging sponge (DHS) reactor to recover after a 10-day outage. The DHS tested in this study uses polyurethane sponge as packing material. This full-scale DHS reactor has been tested over a period of about 4 years in India with a flow rate of 500 m 3 /day. Water was not supplied to the DHS reactor that was subjected to the 10-day outage; however, the biomass did not dry out because the sponge was able to retain enough water. Soon after the reactor was restarted, a small quantity of biomass, amounting to only 0.1% of the total retained biomass, was eluted. The DHS effluent achieved satisfactory removal of suspended solids, chemical oxygen demand, and ammonium nitrogen within 90, 45, and 90 min, respectively. Conversely, fecal coliforms in the DHS effluent did not reach satisfactory levels within 540 min; instead, the normal levels of fecal coliforms were achieved within 3 days. Overall, the tests demonstrated that the DHS reactor was sufficiently robust to withstand long-term outages and achieved steady state soon after restart. This reinforces the suitability of this technology for developing countries. Graphical abstract: Highlights: A full-scale down-flow hanging sponge (DHS) reactor functions successfully in India. We subjected this reactor to a 10-day outage to evaluate its resilience. SS, COD, and NH4 + contents were good 90, 45, and 90 min after restart, respectively. Only 0.1% of the total biomass held in the DHS reactor was eluted after restart. This DHS can withstand outages and achieved steady state soon after restart.